Anonymous security authentication scheme using elliptic curve cryptography and hash function in mobile network - Yuehui CHEN; Miao HUANG (Dianxin kexue)
In order to prevent personal data from being lacked and improve the existing mobile network roaming anonymous authentication scheme,anonymous security authentication scheme using elliptic curve cryptography and hash functions in mobile network was proposed.With elliptic curve cryptography and hash functions,random numbers were used to replace public key encryption and time stamp.Firstly,before using the roaming services of a foreign agent（FA）,hash function was calculated.A host agent（HA）was used by mobile user to register.Then,authentication and session key were set up with elliptic curve encryption.If HA is always in FA,MU can update the session key with FA.Finally,through a common channel,MU could utilize HA to change their passwords.The analysis of the performance and safety shows that,compared with other similar programs,the proposed scheme has significantly improved efficiency and safety.And the virtual computing time is only 2.000 85 seconds,which sharply reduces the cost of computing.